2012
DOI: 10.1038/nature10936
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule inhibitors of the AAA+ ATPase motor cytoplasmic dynein

Abstract: The conversion of chemical energy into mechanical force by AAA+ (ATPases associated with diverse cellular activities) ATPases is integral to cellular processes, including DNA replication, protein unfolding, cargo transport, and membrane fusion1. The AAA+ ATPase motor cytoplasmic dynein regulates ciliary trafficking2, mitotic spindle formation3, and organelle transport4, and dissecting its precise functions has been challenging due to its rapid timescale of action and the lack of cell-permeable, chemical modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
381
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(420 citation statements)
references
References 30 publications
29
381
0
Order By: Relevance
“…This upregulation was blocked by pretreating cells with CBD, a small molecule which inhibits the dynein motor protein responsible for trafficking microtubules to primary cilia (Firestone et al, 2012). Notably, although CBD treatment reduces the size and number of primary cilia, it also regulates mitotic spindle formation and organelle transport (Firestone et al, 2012). Thus, our interpretation does not account for the possibility that our observed effects might result from non-specific effects of CBD.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This upregulation was blocked by pretreating cells with CBD, a small molecule which inhibits the dynein motor protein responsible for trafficking microtubules to primary cilia (Firestone et al, 2012). Notably, although CBD treatment reduces the size and number of primary cilia, it also regulates mitotic spindle formation and organelle transport (Firestone et al, 2012). Thus, our interpretation does not account for the possibility that our observed effects might result from non-specific effects of CBD.…”
Section: Discussionmentioning
confidence: 54%
“…We used an in vitro system to apply low-magnitude flow to endothelial cells to model endocardial, cilia-dependent flow responses and found that flow stimulated Notch1, Efnb2 and Nrg1 expression in the absence of myocardially derived factors or circulating factors in the bloodstream. This upregulation was blocked by pretreating cells with CBD, a small molecule which inhibits the dynein motor protein responsible for trafficking microtubules to primary cilia (Firestone et al, 2012). Notably, although CBD treatment reduces the size and number of primary cilia, it also regulates mitotic spindle formation and organelle transport (Firestone et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CA2 disrupts cytoplasmic microtubules without affecting basal bodies. Ciliobrevin, a small molecule that inhibits ciliogenesis through the inhibition of cytoplasmic dynein, also disrupts microtubule organization and γ-tubulin localization (49).…”
Section: Discussionmentioning
confidence: 99%
“…On a basic science level, these membrane-permeable compounds provide the scientific community with a tool for the targeted and functional inhibition of a given protein in the cell; a potent means of evaluating the intracellular functions of that protein [1,2]. From a biomedical standpoint, the characterization of these small-molecule inhibitors affords an opportunity for the development of novel disease treatments centering on the repression of an offensive molecule or the reversal of its downstream effects [3][4][5].…”
Section: Introductionmentioning
confidence: 99%